Preferential Life Partner For User Mass Journalism Dating Application (Gen Z Case Study) - Taufiq Sarfan Hasibuan; M. Yoserizal Saragih (Jurnal Info Sains : Informatika dan Sains, 2024)
In research this, investigated challenges faced Generation Z in use application date For build sustainable relationship. Introduction explain complexity in choose partner potential and risks dishonesty in representation online self who can disrupting the process of trust and intimacy. Research methods involve interview deep with user application date Generation Z for understand experience and perception they to dynamics This. Research result show that Lots from they experience difficulty in navigate High expectations and low expectations realistic to candidate partner, as well face challenge in build deep trust and intimacy in online relationships.